Une démarche d’ergonomie de la formation - Zoya Horcik; Marc Durand (Activités)
This paper describes a cooperation between professionals from the Geneva’s University Hospitals and our research unit, dealing with a vocational training program for nurses anesthetists using simulation at the SimulHUG Center. Our ergonomic approach of vocational education is presented, based on the assumption of autonomy of the human activity (Theureau, 2004, 2006). This current program counts, at the moment, three stages. After a quick presentation of the training device’s first version, we summarize the typical results obtained in Step 2 and areas of possible enrichment planned. The conclusion briefly discusses the nature of relationship between researchers, trainers and principles of cooperation among them.